Dumb clucks - Stine, R. L.; Park, Trip (New York : HarperCollins, 2007)
Bernie Bridges finds himself caught in a schoolyard battle between the Clucks and the Quacks after his idea to sell t-shirts featuring a popular cartoon character backfires.
"A Parachute Press book.".
3.7
3-6
Keywords: Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction; Television programs -- Juvenile fiction; Boarding schools -- Fiction; Schools -- Fiction; Television programs -- Fiction; Private schools -- Fiction; School stories; Television programs -- Fiction